2022
DOI: 10.1002/ijgo.14387
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative morphologic changes of the isthmocele and clinical impact in patients treated by channel‐like (360°) hysteroscopic technique

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
4
0
3
Order By: Relevance
“…Some reports have shown that RMT was increased by resectoscopic surgery, whereas others did not significantly influence RMT 71,98–101 . This difference may be attributed to different procedures of hysteroscopic surgery.…”
Section: Hysteroscopic Surgery In Women With Csdimentioning
confidence: 88%
See 1 more Smart Citation
“…Some reports have shown that RMT was increased by resectoscopic surgery, whereas others did not significantly influence RMT 71,98–101 . This difference may be attributed to different procedures of hysteroscopic surgery.…”
Section: Hysteroscopic Surgery In Women With Csdimentioning
confidence: 88%
“…Shi et al 99 Some reports have shown that RMT was increased by resectoscopic surgery, whereas others did not significantly influence RMT. 71,[98][99][100][101] This difference may be attributed to different procedures of hysteroscopic surgery. In our study, only the inferior edge of the CSD was resected, and the entire isthmus was cauterized using a ball electrode.…”
Section: Hys Teroscopi C Surg Ery In Women With C S D Imentioning
confidence: 99%
“…As pacientes podem abordar os sintomas de maneira conservadora, mas, quando persistentes ou relacionados a problemas de fertilização, esse defeito pode exigir correção cirúrgica 2,4 . Além das manifestações clínicas supracitadas, essas pacientes apresentam risco aumentado de desenvolvimento de placenta prévia, deiscência de cicatriz, gravidez ectópica na cicatriz de cesariana e ruptura uterina 1,5 .…”
Section: Introductionunclassified
“…Brazilian Journal of Development, Curitiba, v.9, n.9, p. 26725-26738, sep., 2023 A fisiopatologia da istmocele ainda não é completamente elucidada, mas estudos demonstram que a presença de fatores relacionados tanto ao procedimento cirúrgico quanto ao organismo da paciente pode estar associada ao seu aparecimento 1,3,5 . Em relação à técnica operatória aplicada, a realização de incisões uterinas muito baixas é um fator de risco para o desenvolvimento de istmocele 3,5 .…”
Section: Introductionunclassified
See 1 more Smart Citation